Juridical Analysis Of Land Allocation Agreements Regarding Efforts To Take Over Land By BP Batam - Siburian, Hasoloan; Sudirman, Lu; Syarief, Elza (Universitas Internasional Batam, 2024)
This research generally aims to determine the role of the Batam Concession Agency and the strategy of the Batam Concession Agency in managing land related to the existence of idle land. The research method used in this research is the normative juridical research method, namely a research method whose main data is obtained from statutory regulations. Based on the research results obtained and analyzed by land researchers in Batam City, it is regulated based on PERKA No. 3 of 2020 concerning the Implementation of Land Allocation, Land Rights in Batam City are divided into two, namely, HGB for 30 years and can be extended for 25 years, and Right to Use for 25 years and can be extended for 20 years, both rights can be renewed according to their interests . The position of the land agreement in Batam City is a product issued by BP Batam. The land agreement is made based on the request of the beneficiary of the Right to Get the approval from the head of BP Batam. Regarding idle land in the city of Batam, it is divided into two, land that has not yet completed administration and idle land that has completed administration but has not been utilized properly.